NORMAL BUSINESS FLOW OF STREET VENDORS -POST COVID -19 WITH SPECIAL REFERENCE TO THOOTHUKUDI DISTRICT - V, Susganthi; Nallathambi, J. Immanuel (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Street vendors constitute an integral and legitimate part of the urban retail trade and distribution system for daily necessities of the general public. They represent 4% of the urban workforce across India and play a variety of roles in city life. The street vending economy approximately has a parallel turnover of Rs 80 crore a day and every street entrepreneur or trader supports an average of three others as employees or partners or workers on commission. Street vending which is otherwise known as flea market is an inseparable constituent of the urban informal economy. When it comes to street vending, the amount of investment and skills required is low, which makes it a relatively accessible opportunity for everyone to earn their livelihood. Due to the lockdown enforced by the government because of COVID-19, the street vending sector has been severely impacted and the street vendors bore the brunt of it. There are approximately 4 crore street hawkers in India – of which 1/3rd consists of women, who support their families to provide an extra cushion of income. About 82 per cent of the workforce of India is working in the unorganized sector according to the National Sample Survey Office (NSSO). Coronavirus crisis had exposed a widespread lack of awareness about the importance of street vendors to the nation’s overall economy.In India, the informal sector contributes to 7% of the country’s GDP. According to the International Labor Organization, COVID-19’s impact on the informal sector is equivalent to 195 million jobs lost.